Some dynamical calculations of a transducer of two constact points type with two degrees of freedom - Do Trong Hung; Nguyen Van Khang; Do Sanh; Banh Xuan Tho; Ho Dac Tho (Vietnam Journal of Mechanics)
As it is known, in machine-building two methods are used for checking the size of manufacturing details: the method of active check and the method of passive check and in connection with this there are two checking remedies: that of active check and passive check